2021
DOI: 10.3904/kjim.2019.153
|View full text |Cite
|
Sign up to set email alerts
|

Effect of corticosteroid therapy in the early phase of acute respiratory distress syndrome: a propensity-matched cohort study

Abstract: Background/Aims: It is unclear whether corticosteroid use in patients with acute respiratory distress syndrome (ARDS) improves survival. This study aimed to investigate whether the administration of corticosteroids to patients in the early phase of moderate to severe ARDS is associated with improved outcomes. Methods: We analyzed the data of patients who received corticosteroids within 7 days of the onset of ARDS between June 2006 and December 2015 at a single tertiary teaching hospital. A total of 565 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
(34 reference statements)
2
9
1
Order By: Relevance
“…In the randomized controlled trial by Tongyoo et al [6], administration of corticosteroids was not associated with 28-day mortality (22.5% vs. 27.3%, relative risk, 0.82; 95% CI, 0.50 to 1.34; p = 0.51), in line with the findings of Baek et al [9]. By contrast, a recent randomized controlled trial by Villar et al [7] showed that treatment with corticosteroids was associated with decreased mortality at day 60 (21% vs. 36%; between group difference, −15.3%; 95% CI, −25.9 to −4.9; p = 0.0047).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…In the randomized controlled trial by Tongyoo et al [6], administration of corticosteroids was not associated with 28-day mortality (22.5% vs. 27.3%, relative risk, 0.82; 95% CI, 0.50 to 1.34; p = 0.51), in line with the findings of Baek et al [9]. By contrast, a recent randomized controlled trial by Villar et al [7] showed that treatment with corticosteroids was associated with decreased mortality at day 60 (21% vs. 36%; between group difference, −15.3%; 95% CI, −25.9 to −4.9; p = 0.0047).…”
supporting
confidence: 70%
“…In an article published in The Korean Journal of Internal Medicine, Baek et al [9] report the results of a propensitymatched cohort study that investigated the effect of corticosteroids administered in the early phase of ARDS. In that study, the use of corticosteroids was not associated with 28 days (odds ratio [OR], 1.031; 95% confidence interval [CI], 0.657 to 1.618; p = 0.895) and 90 days (OR, 1.435; 95% CI, 0.877 to 2.348; p = 0.151) mortality rates after adjusting propensity scores.…”
mentioning
confidence: 99%
“…It is not known if there may be a multifactorial increase in susceptibility to barotrauma related to inflammation as suggested by Wali et al 7 Baek et al found a correlation between PTX and steroid use in ARDS patients, but this relationship may be due to confounders such as longer duration of ventilation. 15 Other studies have not found this relationship. 16 Larger studies are needed to determine if a relationship exists between steroid administration and barotrauma in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 92%
“…One confusing area has been the use of corticosteroids, which are beneficial in critically ill patients, but their use has been debated in SARS-CoV-2. In our case, the patient was previously on prednisone for tubulointerstitial nephritis, and therapy was continued mostly to avoid adrenal insufficiency [22][23][24].…”
Section: Discussionmentioning
confidence: 91%